Low Penetrance Pancreatitis Phenotype in a Venezuelan Kindred with a PRSS1 R122H Mutation - Solomon, Sheila; Gelrud, Andres; Whitcomb, David C (JOP. Journal of the Pancreas, 2013)
Context Hereditary pancreatitis is typically caused by the PRSS1 R122H or N29I mutations resulting in high penetrance (about 80%) autosomal dominant disorder that is usually reported in North America, Northern Europe and Northeast Asia, but not South America, Africa or India. Case report Here we report a kindred from Venezuela, South America with the PRSS1 R122H variant. Only the proband, an 11-year old boy with severe chronic pancreatitis, and a maternal grandmother with pancreatitis at age 60 years (confirmed PRSS1 R122H), are symptomatic. Conclusions Issues of mutation prevalence, non-penetrance, and disease recognition in various countries are discussed. Image: Pedigree of a Venezuelan kindred.